Analisa Struktur Sosial Ekonomi Masyarakat untuk Mendukung Pembangunan Desa (Studi Kasus Desa Setabu, Kecamatan Sebatik, Kabupaten Nunukan, Provinsi Kalimantan Timur) - Amongjati, Sri Anom; Sjaf, Sofyan; Mahardika, Afan Ray (Program Studi Agribisnis, Fakultas Pertanian, Universitas Singaperbangsa Karawang, 2024)
The Village Law mandates that village development be carried out independently by village, regional and national governments as well as through multi-stakeholder collaboration, so a proper analysis of the socio-economic situation in the village is needed. This research wants to present an analysis of socio-economic structure as an approach to creating appropriate village development planning, both for communities and families. Through the interview process and Focus Group Discussion (FGD) with stakeholders as well as a census of all family heads in the Village, it was found that qualitative and quantitative approaches could be used as a method for analyzing socio-economic structures based on social layers of society as a reference for development in the Village. Qualitative analysis can be used as a reference for development at the community level, while quantitative analysis can be used as a reference for development at the family and household level. These two approaches can be a reference for stakeholders in planning development so that development allocation is right on the problem and right on the subject of development in the village.